KINERJA PETUGAS OPERASIONAL PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA BUKITTINGGI - Heru Pratama Rosyidin; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The performance of the department cleanliness and landscaping of Bukittinggi in waste management in the city of Bukittinggi in handling the amount of trash scattered and lack of bins supplied does not match the number of inhabitants. To be clear, we propose the following research question: "How Performance operational officer on duty cleanliness and landscaping city bukittinggi" purpose in this study was Want to know how is the performance of the performance of the operational officers in the department cleanliness and landscaping in the city of Bukittinggi. The research method here the authors use descriptive research and data collection techniques used in this research is observation, interview, documentation, using qualitative techniques in which the collected data is processed and qualitatively. From the results of the data shows that based on the research and discussion that has been described, it can be concluded that the quality performance of operational personnel and Landscaping Bukittinggi is not maximized. Location shelters while still a ride on the roadside. Transporting procedure is not optimal because of the lack of quantity fleet used so that the working time is not efficient. Department of Hygiene and Bukittinggi should have more than one location of temporary shelters and spread in order to avoid the accumulation of garbage. On the transport procedure, should the fleet used to transport garbage from the garbage temporary shelters to landfills must be fixed and added that the quality of the officer's performance can be more efficient.Keywords: Performance janitor, quality, quantity